Multimethod Assessment of the Cyclic Fatigue Strength of ProGlider, Edge Glide Path and R-Pilot Endodontic Instruments - Jorge N. R. Martins; Duarte Marques; Isabel Vasconcelos; Sofia Arantes-Oliveira; João Caramês; Francisco Manuel Braz Fernandes (MDPI AG, 2022)
Background: The aim of this study was to comprehensively evaluate the cyclic fatigue strength of ProGlider, Edge Glide Path, and R-Pilot instruments. Methods: Sixty-three instruments were submitted to a multimethod evaluation. Their design was analyzed by stereomicroscopy and scanning electron microscopy, including the number of blades, helical angle means, cross-sectional design, surface finishing, and symmetry. Energy-dispersive X-ray spectroscopy was used determine the nickel/titanium elements ratio, and differential scanning calorimetry determined the instruments' phase transformation temperatures. The cyclic fatigue tests were conducted in an artificial canal with a 6 mm radius and 86 degrees of curvature. The Mood's median test and one-way ANOVA were used to determine differences, with the significance level set at 0.05. Results: The ProGlider presented the highest number of blades (n = 21), while R-Pilot had the highest helical angles (26.4°). Differences were noted in the instruments' cross-sections and surface finishing. The ProGlider and R-Pilot showed some similarities regarding the phase transformation temperatures but differed from the Edge Glide Path. All alloys showed an almost equiatomic nickel/titanium ratio. The R-Pilot instruments showed a significantly higher (p < 0.05) time to fracture than both the other files. Conclusion: Reciprocating R-Pilot instruments showed a higher cyclic fatigue time to fracture than the ProGlider and Edge Glide Path rotary files.